BIMBINGAN TEKNIS PENGOLAHAN BAKSO AYAM PLUS BAGI USAHA RUMAH TANGGA DI KELURAHAN RAHANDOUNA KECAMATAN POASIA KOTA KENDARI - Limi, Muhammad Aswar; Zani, Munirwan; Abdullah, Sukmawati; Nalefo, La; Rianse, Muhammad Iqbal Kusumabaka (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2023)
This service aims to improve meatball products and diversify chicken meatball products in Rahandouna Village, Poasia District, Kendari City. Service activities will be carried out from March 2023 to May 2023. This activity connects universities, the government, and local communities to answer problems in entrepreneurship development in Rahandouna District. The population and respondents are the people of Rahandouna District who are involved in the chicken meatball business. The problem-solving framework for this service activity focuses on improving meatball products and diversifying chicken meatball products. The material that will be presented includes improving food processing (chicken meatballs) by implementing suitable food production methods (CPPB) / good manufacturing practices (GMP) and interactive discussions after delivering the material. The devotion variable is the chicken meatball processing technique. An analytical tool to measure the effectiveness of technical guidance through conversations with participants was carried out to assess increases in knowledge and skills. Data analysis uses descriptive statistical methods to measure changes in understanding of CPPB/GMP. Based on the results of the Technical Guidance activity for Processing Chicken Meatballs Plus for Household Businesses in Rahandouna Village, Poasia District, Kendari City, it can be concluded that creativity in processing and serving has succeeded in improving the quality and diversification of chicken meatball products with various exciting variants.